Fabrication of TiO2 nanofiber membranes by a simple dip-coating technique for water treatment - Zhang, Qi; Wang, Hua; Fan, Xinfei; Lv, Fenghe; Chen, Shuo; Quan, Xie (Surface & coatings technology, 2016)
A TiO2 nanofiber membrane was fabricated by coating TiO2 nanofibers on a ceramic hollow fiber membrane support using a simple dip-coating technique. Scanning electron microscopy reveals that the TiO2 nanofibers uniformly cover the entire surface of the membrane, and the anatase crystal phase of TiO2 is present based on X-ray diffraction spectroscopy data. The TiO2 nanofiber membrane has a porosity of about 80% and a pure water flux of 1700L/(m2·h). Meanwhile, the performance of this TiO2 nanofiber membrane was evaluated using humic acid (HA) as a test substance, and a high HA removal of 90% is achieved. This approach provides a simple technique for fabricating photocatalytic membranes for water treatment. [Display omitted] •A functional membrane was fabricated by coating TiO2 nanofibers on a membrane.•The TiO2 nanofiber membrane has a pure water flux of 1700L/(m2·h).•A high humic acid removal of 90% is achieved.